Study on Effects of Processing with Vinegar and Saline on Toxicity and Anti-diabetic Property of Citrullus colocynthis (L.) Schrad. Fruit Extract in Rats - H Fallah Huseini; S Kianbakht; R Mousavi; N Aman Zadeh (Institue of Medicinal Plants, ACECR, 2011)
Background: The fruits of Citrullus colocynthis are used for treatment of diabetes. C. colocynthis has controlled blood glucose levels in diabetic animals and type 2 diabetic patients. C. colocynthis is toxic at high doses so it is soaked in vinegar or saline for a while in order to reduce its toxicity. Objective: The effects of processing with vinegar and saline on the toxicity and anti-diabetic property of C. colocynthis in rats were studied. Methods: Determination of LD50 (median lethal dose): The non-processed and saline and vinegar processed hydro-alcoholic extracts of C. colocynthis were administered via gavage to groups of 10 healthy male and female Wistar rats at various doses once and the number of dead animals in each group within 72 hours was determined. Study on anti-diabetic effect: Male Wistar rats were made diabetic with the intra-peritoneal injection of 125 mg/kg alloxan. Each extract was administered via gavage to a group of 10 diabetic male Wistar rats at the daily dose of 20 mg/kg for 1 month and finally, the tail venous blood glucose levels after fasting for 8 hours were determined with the glucose oxidase method. Results: The LD50s of the non-processed and saline and vinegar processed extracts were 200 mg/kg, 250 mg/kg and 250 mg/kg respectively. The three extracts reduced the blood glucose levels significantly compared with control (p < 0.05). Conclusion: Processing with saline or vinegar can reduce the toxicity of C. colocynthis with maintenance of its anti-diabetic effect.